An evaluation on industrial applications using leakage inductance and series capacitance converter (2025)
The Leakage Inductance and Series Capacitance (LLSC) resonant converters are exhaustively employed in a wide assortment of industries involving consumer electronics due to their benefits of good efficiency, higher power density, immunity to electromagnetic interference, low EMI and harmonic distortion, wide production extends, voltage stress is lowered and frequency at high operating characteristic. Three of the most prominent converters with LLSC topologies are explored along with thorough analyses of their merits and disadvantages. The background of LLSC resonant converters are also discussed. A significant amount of research is also being done regarding large - scale production of LLSC resonant converters, namely in order to charge electric automobiles (EVs), solar systems, LED lighting drivers, and power supply for LCD TVs. Eventually, the growth of LLSC resonant converter is explained.